BOugie or stylet in patients UnderGoing Intubation Emergently (BOUGIE): protocol and statistical analysis plan for a randomised clinical trial. Issue 5 (25th May 2021) - Driver, Brian; Semler, Matthew W; Self, Wesley H; Ginde, Adit A; Gandotra, Sheetal; Trent, Stacy A; Smith, Lane M; Gaillard, John P; Page, David B; Whitson, Micah R; Vonderhaar, Derek J; Joffe, AM; et al.
Abstract : Introduction: Intubation-related complications are less frequent when intubation is successful on the first attempt. The rate of first attempt success in the emergency department (ED) and intensive care unit (ICU) is typically less than 90%. The bougie, a semirigid introducer that can be placed into the trachea to facilitate a Seldinger-like technique of tracheal intubation and is typically reserved for difficult or failed intubations, might improve first attempt success. Evidence supporting its use, however, is from a single academic ED with frequent bougie use. Validation of these findings is needed before widespread implementation. Methods and analysis: The BOugie or stylet in patients Undergoing Intubation Emergently trial is a prospective, multicentre, non-blinded randomised trial being conducted in six EDs and six ICUs in the USA. The trial plans to enrol 1106 critically ill adults undergoing orotracheal intubation. Eligible patients are randomised 1:1 for the use of a bougie or use of an endotracheal tube with stylet for the first intubation attempt. The primary outcome is successful intubation on the first attempt. The secondary outcome is severe hypoxaemia, defined as an oxygen saturation less than 80% between induction until 2 min after completion of intubation. Enrolment began on 29 April 2019 and is expected to be completed in 2021. Ethics and dissemination: The trial protocol was approved with waiver of informed consent by the Central Institutional Review Board at Vanderbilt University Medical Center or the local institutional review board at an enrolling site. The results will be submitted for publication in a peer-reviewed journal and presented at scientific conferences. Trial registration number: ClinicalTrials.gov Registry (NCT03928925 ).